2014
DOI: 10.1039/c4cp00172a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of an unsymmetrical, ether-linked, fluorinated bimesogen exhibiting a new polymorphism containing the NTB or ‘twist-bend’ phase

Abstract: In this article we report on the liquid crystal phases and properties of the bimesogen 4-((11-((4'-fluoro-[1,1'-biphenyl]-4-yl)oxy)undecyl)oxy)-2,3-difluoro-4'-(4-propylcyclohexyl)-1,1'-biphenyl. This material was shown to exhibit an Iso Liq-N-NTB-SmA phase sequence, thereby clearly indicating that the NTB phase possesses an ordering of the constituent molecules that is between that of a conventional nematic and the smectic A phase. This compound allows us to better understand the relationship between molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 18 publications
11
90
0
Order By: Relevance
“…In recent years there has been a resurgence of interest in liquid‐crystal dimers and bimesogens, driven by interest in wide temperature range blue phases,1, 2 flexoelectric behaviour3, 4, 5 and the ability of some dimeric materials to exhibit a lower‐temperature mesophase lacking lamellar organisation thereby being described as nematic 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. This lower temperature ‘nematic’ phase is denoted N X or N TB ,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 in which ‘X’ and ‘TB’ refer to unknown and twist‐bend, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there has been a resurgence of interest in liquid‐crystal dimers and bimesogens, driven by interest in wide temperature range blue phases,1, 2 flexoelectric behaviour3, 4, 5 and the ability of some dimeric materials to exhibit a lower‐temperature mesophase lacking lamellar organisation thereby being described as nematic 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. This lower temperature ‘nematic’ phase is denoted N X or N TB ,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 in which ‘X’ and ‘TB’ refer to unknown and twist‐bend, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This lower temperature ‘nematic’ phase is denoted N X or N TB ,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 in which ‘X’ and ‘TB’ refer to unknown and twist‐bend, respectively. The local structure of the N X /N TB phase is still hotly debated, with the heliconical ‘twist‐bend’ model proposed independently by Meyer19 and Dozov20 supported by 2 H NMR studies, measurement of the electroclinic effect, freeze‐fracture transmission electron microscopy (FFTEM) and carbon K‐edge SAXS 21, 22, 23, 24.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the new inhomogeneous nematic phases have been observed [1][2][3][4][5][6][7][8][9][10][11][12][13], and the study of the detailed structure of these phases is currently the most topical issue in liquid crystals research. The experiments for oligomers and bent-core systems indicate that there are at least two types of modulated nematic structures with one-dimensional periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we opted to prepare a material incorporating the 2,3-difluorobiphenylcyclohexyl (DFBC) unit employed in the first ether-linked bimesogen to exhibit the N TB phase, FBO 11 ODFCB 3 [62]. We have found previously that dimers and bimesogens incorporating the DFBC unit have a strong tendency to exhibit the twist-bend nematic phase [63].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that many functional groups -including the SF 5 groupcan be incorporated into the structure of a suitable dimer without loss of the N TB phase. Last, the twistbend nematic phase -in dimers and bimesogens at least -is found mostly for methylene-linked materials, although a number of other linking groups are known to yield materials that afford this mesophase [7,21,22,33,[44][45][46][47][48][49]. In the first part of this paper, we present the latest part of our study into the structureproperty relationships of bis ether-linked dimers and bimesogens that exhibit the twist-bend phase.…”
Section: Introductionmentioning
confidence: 99%